2019
DOI: 10.1111/apa.14699
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐to‐skin contact during eye examination did not reduce pain compared to standard care with parental support in preterm infants

Abstract: Aim: We compared the pain relieving effect of skin-to-skin contact versus standard care in the incubator during screening for retinopathy of prematurity.Methods: This randomised crossover study included 35 preterm infants of less than 32 weeks of gestational age admitted to St Olavs University Hospital, Trondheim, Norway, between January 2014 and June 2016. Randomisation was for skin-to-skin with one of the parents or standard care with supportive positioning by parents for the first of two consecutive eye exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Almost half of the included studies, 44 papers, reported on SSC with parents for neonatal pain relief, but only one included fathers in the intervention (66). The papers were published from 2000 to 2020, with nine from the USA, eight from India, seven from Iran, six from Canada, and the rest from various places around the world.…”
Section: Skin-to-skin Contactmentioning
confidence: 99%
“…Almost half of the included studies, 44 papers, reported on SSC with parents for neonatal pain relief, but only one included fathers in the intervention (66). The papers were published from 2000 to 2020, with nine from the USA, eight from India, seven from Iran, six from Canada, and the rest from various places around the world.…”
Section: Skin-to-skin Contactmentioning
confidence: 99%
“…However, these authors assigned the PIPP score separately for each phase of fundoscopy, that is, speculum insertion, indirect ophthalmoscopy and scleral indentation during indirect ophthalmoscopy, and reported the average for the entire examination, so these results are not comparable to ours (Cogen et al 2011). In another study by Kristoffersen et al, two methods of pain relief were compared during ROP examinations (Kristoffersen et al 2019). Premature Infant Pain Profile (PIPP) score during eye examination (digital imaging) with skin-to-skin contact versus standard care with parental support in the intubator was found to be 10.2 versus 10.3, respectively; however, again, these figures are not directly comparable to ours for a number of reasons.…”
Section: Cohen Et Al Reported a Mean (Sd)mentioning
confidence: 87%
“…In another study by Kristoffersen et al., two methods of pain relief were compared during ROP examinations (Kristoffersen et al. 2019). Premature Infant Pain Profile (PIPP) score during eye examination (digital imaging) with skin‐to‐skin contact versus standard care with parental support in the intubator was found to be 10.2 versus 10.3, respectively; however, again, these figures are not directly comparable to ours for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 11 of the 22 included studies were parallel-group RCTs (Akcan et al, 2009;Castral et al, 2008;de Sousa Freire et al, 2008;Dezhdar et al, 2016;Gao et al, 2015;Holsti et al, 2011;Kostandy et al, 2008;Olsson et al, 2016;Sen & Manav, 2020;; V. V. , and 11 were randomized crossover trials (Axelin et al, 2006(Axelin et al, , 2009Cong et al, 2009Cong et al, , 2011Cong et al, , 2012Johnston et al, 2003Johnston et al, , 2008Johnston et al, , 2009Kristoffersen et al, 2019;Ludington-Hoe et al, 2005;Nimbalkar et al, 2013). Five studies were conducted in the United States (Cong et al, 2009(Cong et al, , 2011(Cong et al, , 2012Kostandy et al, 2008;Ludington-Hoe et al, 2005), six were conducted in Europe (Akcan et al, 2009;Axelin et al, 2006Axelin et al, , 2009Kristoffersen et al, 2019;Olsson et al, 2016;Sen & Manav, 2020), four were conducted in Canada (Holsti et al, 2011;Johnston et al, 2003Johnston et al, , 2008Johnston et al, , 2009, two were conducted in Brazil (Castral et al, 2008;de Sousa Freire et al, 2008), three were conducted in India (Nimbalkar e...…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%